Eltrombopag treatment in thrombocytopenia following hematopoietic stem cell transplantation: A multicenter real-world experience - Kılıç Güneş, Ebru; Yiğit Kaya, Süreyya; Yaman, Fatih; Yeniay, Mustafa Kemal; Vural, Kurtuluş; Cömert, Melda; Sevindik, Ömür Gökmen; Andıç, Neslihan; Dağdaş, Simten; Nizam Özen, İlknur; Kaynar, Leylagül; Yavaşoğlu, Filiz; et al. (My University, 2024)
Introduction: Thrombocytopenia is among the most common complications following hematopoietic stem cell transplantation and is associated with increased mortality and morbidity with no standard treatment yet. In this multicenter and retrospective study, we aim to present our multi-center experience of Eltrombopag treatment in patients with isolated thrombocytopenia following HSCT. Material-method: A total of 73 patients from 5 centers who underwent autologous or allogeneic stem cell transplantation, had no primary disease relapse, all of whom had neutrophil engraftment, complete chimerism, and who were diagnosed with Prolonged Isolated Thrombocytopenia (PIT) or Secondary Failure Of Platelet Recovery (SFPR) were included in the study. The patients were initiated on Eltrombopag at a dose of 50–150 mg. Complete response was defined as a platelet count >50×109/L for 7 consecutive days with no transfusion support. Results: A total of 50.3% of the patients underwent Autologous and 49.7% Allogeneic Stem Cell Transplantation, 54.8% were diagnosed with PIT, and 45.2% were diagnosed with SFPR, and the treatment with 50–150 mg/day Eltrombopag was initiated on the median day +42. Complete response was achieved in 71.2% of these patients on the median day 23 of the treatment. No significant effects of the initial dose (50–150 mg/day) were detected in the Complete Response in the multivariate analysis on response. An insufficient number of Megakaryocytes in the bone marrow before Eltrombopag treatment was determined as an independent risk factor in determining the response (OR 3.57, 95% CI 1.21–10.55). The overall survival of the patients who did not respond to Eltrombopag was found to be significantly worse than that of patients who responded (p=0.022, HR:2.74, 95% CI 1.12–6.54). Conclusion: As a result of the present study, Eltrombopag treatment was found to be effective and safe in thrombocytopenia that develops following hematopoietic stem cell transplantation. It was concluded that its use may be more effective in patients with sufficient bone marrow megakaryocytes before the treatment and an initial dose of 50 mg/day may be appropriate in terms of cost, effectiveness, and toxicity. Large-scale randomized and controlled prospective studies are needed to determine the roles of Eltrombopag treatment in patients with post-transplant PIT and SFPR.
Keywords: Eltrombopag; Stem Cell Transplatation; Thrombocytopenia